Formulation and in vitro evaluation of theophylline anhydrous bioadhesive tablets - Deshmukh, V N; Jadhav, J K; Sakarkar, D M (Asian Journal of Pharmaceutics (AJP), 2014)
The aim of the current study was to design oral controlled release (CR) theophylline anhydrous bioadhesive tablets and to optimize the drug release profile and in vitro bioadhesion strength. Different types of natural hydrophilic polymers such as xanthun gum, locust bean gum, guar gum, karaya gum, and their combinations were used to formulate matrix tablets. Tablets of anhydrous theophylline were prepared by the direct compression method and were subjected to in vitro drug dissolution for 12 hours using the USP dissolution apparatus basket type at a speed of 100 rpm and temperature of 37 Â± 0.5Â°C using gastric fluid (pH 1.2). The bioadhesive strength of the tablets was measured as the force of detachment against the porcine gastric mucosa. The in vitro release study as well as the retention time of the bioadhesive tablets on the mucous membrane were investigated to develop a bioadhesive polymer-based CR delivery system and to evaluate the performance of such a delivery device. The combination of karaya gum:guar gum (6:4) tablet showed a greater bioadhesive strength as compared with a single gum and other gum combination tablets. Karaya gum:guar gum-loaded tablets were not discharged from the mucous membrane and were dissolved in the gastric fluid. An increase in the gum concentration increases the drug release profile beyond 12 hours whereas there is no significant effect of gum concentration on the bioadhesive strength of the tablet.